Effects of Essential Oils on Post Harvest Quality and Shelf Life of Mango (Mangifera Indica L.) (Bangladesh Journal of Botany, 2021)
Effects of essential oils, namely Cinnamon, Citronella, Peppermint, Eucalyptus, Lavender, Thyme, Rosemary, Basil oil enriched coconut oil emulsion on shelf life and quality of ambient stored mango cv. Rangkuai were evaluated. Citronella oil (Cymbopogon nardus) @ 0.5% (v/v) was found to maintain low weight loss (5.14%), high fruit firmness (52.85 N/cm2), ascorbic acid (33.62 mg/100 g), total phenol (89.67 mg/100 g) and least fruit decay (8.33%) at 12 days after storage (DAS) and had delayed accumulation of pulp colour (L: 91.06, a: -2.61, b : 24.03), β-carotene (3.85 mg/100 g) and total sugar (4.46%) for delayed ripening, thus found to extend the shelf life by 7 days compared with control (12.85 days).Bangladesh J. Bot. 50(4): 1143-1149, 2021 (December)